Malaria Vector Surveillance in Kepulauan Seribu as Threat in DKI Jakarta, 2023 - Wahyudi Wahyudi; Mursid Raharjo; Sulistiyani Sulistiyani (Jurnal EduHealth, 2023)
Malaria is a vector borne disease that can affect morbidity and mortality, especially in endemic countries. Malaria cases worldwide in 2017, 219 million cases vector-borne in 2017-2020. Southeast Asian countries especially Indonesia contributed to high cases due to the presence of endemic diseases which were confirmed first by Indonesia at 49.6%, second country India at 36.4%, and third country Myanmar, at 11.5%. The purpose of the surveillance is to find out the malaria control vectors in the area, such as the integration of malaria managers into post-malaria elimination. This study uses observational methods and direct collection of primary or current data specimens. The results of observation showed that there were 3 islands, detected to contain Anopheles Sp. Tidung Island, Lancang Island, and Untung Jawa Island. From the results of observations, it is necessary to provide integration of malaria vector managers in post-malaria elimination, immediately carried out so as not to cause new cases or extraordinary events that were not initially detected, resulting in extraordinary events even though the area has implemented malaria elimination.